A new record of Zatypota albicoxa (Hymenoptera: Ichneumonidae) from Indonesia, with description of a new species of its host spider (Araneae: Theridiidae) - Takasuka, Keizo; Yoshida, Hajime; Nugroho, Putra; Matsumoto, Rikio (Zootaxa, 2011)
Zatypota albicoxa (Walker) is newly recorded from Mt. Merapi, Java Is., Indonesia. This is the first record of Z. albicoxa from this part of the Oriental region and from the Southern Hemisphere, and the first record of the genus Zatypota from Southeast Asia. The Indonesian population of Z. albicoxa attacks a theridiid spider of the genus Parasteatoda, as do populations of Z. albicoxa in other regions. The spider is a new species, and is described under the name of Parasteatoda merapiensis.